Customs and their role in shaping Islamic texts, women's participation and rights as an example - Amin, Abubakr Ali Mohammed (Sulaimani Journal for Humanities, 2026)
Customs have played a major role in directing the behavior and organizing the lives of societies since ancient times. It once replaced the law and then became its source, and it remains the same around the world at different levels. Islam has been aware of this role of customs from the beginning, and therefore acted in a spirit of coup against the culture, customs and traditions of the environment in which it emerged and in which it estimated its early experiences hasn't done it. Instead, he rejected some of the common customs in a reformist spirit, and some of them, after reformulating them, put them into his new worldview, morality and Baha'i framework after the expansion of Muslim power With the advent of the Islamic Empire, Muslims were confronted with the various cultures and customs of new Muslim nations with a cultured past. Muslim scholars did not ignore this fact in the context of jurisprudence, nor did they leave the issue of dealing with customs to the individual tastes of the scholars, but tried to do so in a curricular manner Record the concept of correct and incorrect customs according to their compatibility with the text and Islamic principles and the nature of the relationship between customs and the Islamic text We will come to them in our research, the issue did not stop there. Rather, it extended to the level of shaping Islamic texts, the dominance of customs over its moral, legal, and value references, and the benchmark example of early Islam thanks to the presence of the Prophet himself. It has had various undesirable consequences, especially in relation to the image, role, participation and rights of women. The questions and hypotheses of this study discuss the terrible change of the position of text and custom and the shaping of Islamic text in this regard by custom It is remarkable that customs have shaped Islamic texts in relation to women and their rights and shown the importance of their position.